Enhancement of the enzymatic hydrolysis efficiency of wheat bran using the Bacillus strains and their consortium. (January 2022) - Vu, Vi; Farkas, Csilla; Riyad, Ouahab; Bujna, Erika; Kilin, Akos; Sipiczki, Gizella; Sharma, Minaxi; Usmani, Zeba; Gupta, Vijai Kumar; Nguyen, Quang D.
Graphical abstract: Highlights: Bacillus strains were able to grow and degrade wheat bran releasing soluble sugars. Members of bacterial consortia were selected based on cluster analysis. Consortium of bacterial strains increased significantly cellulolytic activities. Efficacy of the consortium in wheat bran pretreatment was increased significantly. Bacillus consortia showed an increase in cellulose bioconversion than pure cells. Abstract: In the downstream process, the bioconversion of lignocellulosic biomass can be improved by applying a biological pretreatment procedure using microorganisms to produce hydrolytic enzymes to modify the recalcitrant structure of lignocellulose. In this study, various Bacillus strains ( B. subtilis B.01162 and B.01212, B. coagulans B.01123 and B.01139, B. cereus B.00076 and B.01718, B. licheniformis B.01223 and B.01231) were evaluated for the degrading capacity of wheat bran in the submerged medium using enzymatic activities, reducing sugars and weight loss as indicators. The obtained results revealed that the B. subtilis B.01162, B. coagulans B.01123 and B. cereus B.00076 could be promising degraders for the wheat bran pretreatment. Besides, the application of their consortium (the combination of 2–3 Bacillus species) showed the positive effects on cellulose bioconversion compared with monocultures. Among them, the mixture of B. subtilis B.01162 and B. coagulans B.01123 increased significantly the cellulase, endo -glucanase, and xylanase enzyme activity resulting in accelerating the lignocellulose degradation. Our results served a very good base for the development of microbial consortium for biological pretreatment of lignocellulosic raw materials.